Wasiat Wajibah Bagi Anak Angkat dalam Perspektif Hukum Waris Islam - Anggita Probowati; Ahdiana Yuni Lestari (Universitas Muhammadiyah Yogyakarta, 2024)
Adoption is one way of obtaining offspring for married couples who are not blessed with biological children. However, the adoption of this child raises questions in the field of inheritance according to Islamic law, whether the adopted child inherits property or not from his adoptive parents. This research is normative legal research using primary, secondary and tertiary legal materials. The research materials were analyzed descriptively qualitatively. The conclusion is that adopted children can be given inheritance rights by means of an obligatory will from their adoptive parents, a maximum of 1/3 of the available inheritance before being distributed to other heirs. This is in accordance with the provisions of Article 209 KHI